Role of Sufism in the Renewal of the Religious Message - Gulnora Khudayberganova (Penerbit Jurnal Indonesia, 2024)
Today, Islam is experiencing hard times as it had when it first emerged. Moreover, it is labeled with violence and terrorism from the outside, and on the other hand, the false religious and medieval ideology propaganda by Muslim preachers led to introduce Islam as a fanatical and rigid religion. Most of the calls are old in content, based on prejudice, and devoid of spiritual values. The following research examines the method introduced by mysticism and its role in reviving the religious message. The role of Sufi heritage in religious message with its spiritual and moral values, rich history in the revival is analyzed on the basis of the following factors. Renewal of mystical heritage 1) to free mysticism from heresy and superstition 2) new approach towards understanding religious values ​​in harmony with modern realities.